ANALISIS PENGARUH RELIGIUSITAS TERHADAP WILLINGNESS TO VOLUNTEER (STUDI PADA 3 NEGARA: INDONESIA, NIGERIA DAN MESIR) - al latif ms., andi aziz; Widiyanti, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of religiosity on the level of willingness to volunteer among the people of Indonesia, Nigeria and Egypt. The data used is survey data from the World Value Survey (WVS) Wave 7 which was held around 2017 to 2021 and published in 2022, using a purposive sampling technique and filtered using the Isaac and Michael calculation formula. This research is a descriptive quantitative research using multinomial logistic regression analysis technique using secondary data types. From the results of data analysis, it was found that the religiosity variable has a significant effect on the probability of a person's willingness to volunteer at philanthropic institutions in each of the countries that are the research targets, namely Indonesia, Nigeria and Egypt. Thus, the practical implications of this research are as a form of reference for stakeholders as material for consideration and evaluation in policy making to optimize the level of charity activity in philanthropic organizations in these countries in terms of the volunteer aspect and its relation to religiosity.